Democracy and development Focus on Basey I District Multi-Purpose Cooperative. - Paca-anas, Anabelle O. (Tacloban City Anabelle O. Paca-anas, 2009)
Cooperative is an operating type of NGO that have long been recognized as democratic unstitutions for development. They have also been considered as the most effective socio-economic organizations. The government viewed cooperatives as organizations with the capability of securing economies of scale providing the marginalized sectors of society by means of livelihood. The purpose of this study is to examine the interorganizational dynamics of the cooperative with regards to its autonomy and independence. It also tries to know the different linkages of the cooperatives with other non-governmental and governmental institutions, using the following variables Autonomy and Independence, Popular Participation, Linkages/Alliances, Administrative and Financial Capability. I use interviews as the main approach of gathering data and study documents and reports as secondary source of data. I interviewed some pioneering members of the cooperative who have great knowledge and experience. Key informants were selected as main respondents and were identified based on the specific data and information that are needed in the study. This study examines how democratization works in Basey 1 district Multi-Purpose Cooperative through the said variables. Results from these suggest that the Basey 1 District Multi-Purpose Cooperative is promoting democratization and development to its members and to the community.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science